Sexual Objectification of Women in Bath Soap Commercials: A Critical Discourse Analysis of Model Sara Mills - Janchwar Syafutra Zuhudie; Eti Setiawati (Universitas Negeri Semarang, 2026)
Representations of women in commercial media are often trapped in commodification practices that reduce gender identity to mere visual objects. Soap advertisements serve as one of the spaces that consistently exploit the female body to build product appeal through narrow beauty standards. This study aims to examine in depth the practices of sexual objectification of women in soap advertisements through visual and verbal discourse constructions. The research method employed is a descriptive qualitative approach with a Critical Discourse Analysis framework, using Sara Mills' model. The research data sources consist of three video advertisements, namely GIV White Body Wash, LUX Botanicals Body Wash, and Biore Body Foam, selected based on the intensity of visual body representation and their status as contemporary advertisements in the same product category. Data analysis techniques examined subject-object positions and the reader/viewer's position to determine how the text constructs the role of women. The results indicate that sexual objectification functions not only through sensual physical visual displays but also through persuasive language that positions women's skin as the center of commodification within the logic of capitalism. Women are positioned as passive objects whose beauty is validated by an external gaze. At the same time, the self-empowerment narratives presented tend to be pseudo-empowerment as they remain controlled by market interests. This research provides substantial benefits as a theoretical reference in media and gender studies and offers a critical foundation for the development of media literacy in society. Practically, these findings encourage awareness among advertising industry players and consumers to be more critical of ideologies that normalize the objectification of the female body in the public sphere.